Cucurbitacin IIb exhibits anti-inflammatory activity through modulating multiple cellular behaviors of mouse lymphocytes. - Yao Wang; Gao-Xiang Zhao; Li-Hui Xu; Kun-Peng Liu; Hao Pan; Jian He; Ji-Ye Cai; Dong-Yun Ouyang; Xian-Hui He (PLoS ONE, 2014)
Cucurbitacin IIb (CuIIb) is one of the major active compounds in Hemsleyadine tablets which have been used for clinical treatment of bacillary dysentery, enteritis and acute tonsilitis. However, its action mechanism has not been completely understood. This study aimed to explore the anti-inflammatory activity of CuIIb and its underlying mechanism in mitogen-activated lymphocytes isolated from mouse mesenteric lymph nodes. The results showed that CuIIb inhibited the proliferation of concanavalin A (Con A)-activated lymphocytes in a time- and dose-dependent manner. CuIIb treatment arrested their cell cycle in S and G2/M phases probably due to the disruption of the actin cytoskeleton and the modulation of p27(Kip1) and cyclin levels. Moreover, the surface expression of activation markers CD69 and CD25 on Con A-activated CD3(+) T lymphocytes was suppressed by CuIIb treatment. Both Con A- and phorbol ester plus ionomycin-induced expression of TNF-α, IFN-γ and IL-6 proteins was attenuated upon exposure to CuIIb. Mechanistically, CuIIb treatment suppressed the phosphorylation of JNK and Erk1/2 but not p38 in Con A-activated lymphocytes. Although CuIIb unexpectedly enhanced the phosphorylation of IκB and NF-κB (p65), it blocked the nuclear translocation of NF-κB (p65). In support of this, CuIIb significantly decreased the mRNA levels of IκBα and TNF-α, two target genes of NF-κB, in Con A-activated lymphocytes. In addition, CuIIb downregulated Con A-induced STAT3 phosphorylation and increased cell apoptosis. Collectively, these results suggest that CuIIb exhibits its anti-inflammatory activity through modulating multiple cellular behaviors and signaling pathways, leading to the suppression of the adaptive immune response.